The Realization of the Government's Role in Creating Food Security in Indonesia - Indah Megahwati; Sidik Priadana (Ekonomis: Journal of Economics and Business, 2023)
Food is the most important and strategic basic need for human life. Food is a basic need whose fulfillment is the basic right of every human being as stated in Law No. 18 of 2012 concerning food. The type of research used in this research is qualitative research as outlined descriptively. The focus of this research is the role of the government in realizing food security in all regions of Indonesia. By looking at the problems that occur in the field, this research will focus on the government's strategy in realizing food security. The government's role in developing regional food reserves is divided into three, including regulators, facilitators, and dynamicators. The role of the Government as a regulator is to prepare guidelines, directives and references through the issuance of regulations and implement them. The government's role as a facilitator is to create conducive conditions for the implementation of development to bridge various community interests in optimizing regional development, namely by providing facilities in the form of goods and services to support the success of activities. The government's role as a dynamicator is to mobilize community participation if there are obstacles in the development process to encourage and maintain the dynamics of regional development, in this activity, community participation is the involvement of the Rukun Warga and Rukun Tetangga in providing data and identifying recipient data.